Assessment of disease severity and outcome in patients with systemic light-chain amyloidosis by the high-sensitivity troponin T assay - Kristen, Arnt; Giannitsis, Evangelos; Lehrke, Stephanie; Hegenbart, Ute; Konstandin, Matthias; Lindenmaier, David; Merkle, Corina; Hardt, Stefan; Schnabel, Philipp Albert; Röcken, Christoph; Schönland, Stefan; Ho, Anthony Dick; et al. (Blood, 2010)
Cardiac biomarkers provide prognostic information in light-chain amyloidosis (AL). Thus, a novel high-sensitivity cardiac troponin T (hs-TnT) assay may improve risk stratification. hs-TnT was assessed in 163 patients. Blood levels were higher with cardiac than renal or other organ involvement and were related to the severity of cardiac involvement. Increased sensitivity was not associated with survival benefit. Forty-seven patients died during follow-up (22.3 ± 1.0 months). Nonsurvivors had higher hs-TnT than survivors. Outcome was worse if hs-TnT more than or equal to 50 ng/L and best less than 3 ng/L. Survival of patients with hs-TnT 3 to 14 ng/L did not differ from patients with moderately increased hs-TnT (14-50 ng/L), but was worse if interventricular septum was more than or equal to 15 mm. Discrimination according to the Mayo staging system was only achieved by the use of the hs-TnT assay, but not by the fourth-generation troponin T assay. Multivariate analysis revealed hs-TnT, NT-proBNP, and left ventricular impairment as independent risk factors for survival. hs-TnT and NT-proBNP predicted survival, even after exclusion of patients with impaired renal function. Plasma levels of the hs-TnT assay are associated with the clinical, morphologic, and functional severity of cardiac AL amyloidosis and could provide useful information for clinicians on cardiac involvement and outcome.